Extracellular Vesicles: A Potential Biomarker for Quick Identification of Infectious Osteomyelitis - Deng, Songyun; Wang, Yutian; Liu, Shiluan; Chen, Te; Hu, Yanjun; Zhang, Guangyan; Zhang, Xianrong; Yu, Bin (Frontiers in Cellular and Infection Microbiology, 2020)
Effective management of infectious osteomyelitis relies on timely microorganism identification and appropriate antibiotic therapy. Extracellular vesicles (EVs) carry protein and genetic information accumulated rapidly in the circulation upon infection. Rat osteomyelitis models infected by Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Escherichia coli were established for the present study. Serum EVs were isolated 3 days after infection. The size and number of serum EVs from infected rats were significantly higher than those from controls. In addition, bacterial aggregation assay showed that the S. aureus and E. coli formed large aggregates in response to the stimulation of serum EVs from S. aureus-infected and E. coli-infected rats, respectively. Treatment of EVs-S. epidermidis led to large aggregates of S. epidermidis and E. coli, whereas stimulation of EVs-P. aeruginosa to large aggregates of S. aureus and P. aeruginosa. To evaluate the changes in EVs in osteomyelitis patients, 28 patients including 5 S. aureus ones and 21 controls were enrolled. Results showed that the size and number of serum EVs from S. aureus osteomyelitis patients were higher than those from controls. Further analysis using receiver operating characteristic curves revealed that only the particle size might be a potential diagnostic marker for osteomyelitis. Strikingly, serum EVs from S. aureus osteomyelitis patients induced significantly stronger aggregation of S. aureus and a cross-reaction with P. aeruginosa. Together, these findings indicate that the size and number of serum EVs may help in the diagnosis of potential infection and that EVs-bacteria aggregation assay may be a quick test to identify infectious microorganisms for osteomyelitis patients.